If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x + 5r = 3 Reorder the terms: 5r + 13x = 3 Solving 5r + 13x = 3 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-13x' to each side of the equation. 5r + 13x + -13x = 3 + -13x Combine like terms: 13x + -13x = 0 5r + 0 = 3 + -13x 5r = 3 + -13x Divide each side by '5'. r = 0.6 + -2.6x Simplifying r = 0.6 + -2.6x
| 11-(2-4x)=-7 | | 2.3(b+4)=9.77-2b | | 4=3(x-3)-(x-7) | | 12x-30=20x-14 | | 28=y+24 | | 10x^2+16x+4=0 | | 6.9x+3.3=4.4x+10.3 | | -4(5y-10)+2(4y+7)= | | 7+42x=28x+9 | | g^2-10g+8=0 | | 4k-3=k-12 | | log(7-3x)=1.75 | | (x-3)=(2x+24) | | 2x*5=22x | | g^2-10g+19=0 | | 9.8x+19.6=7500x^2 | | (x^2-5x+6)(x^2+4x+3)= | | x-(x*0.2)=0.35 | | 7x+9.89=4x+14 | | 4n+8=6n+4 | | -6a-54=-3-6a+12 | | 11p+12q=79 | | (x^2+2x+1)(x^2+x-6)= | | y=-x^2+9x-14 | | F(x)=xsquared-5x-14 | | 2+3*2*3= | | (X+3)(x+5x-2)= | | 6x+5y+7-4x+2y-11=b | | 5x+25=15x-19 | | 2+3*[2*3]= | | 12x-48-96x+48=8x | | 4x-11=-6X+9 |